Modelling packing arrangements of doxorubicin in liposomal molecules - Kanes Sumetpipat (2018)
© 2016 American Scientific Publishers All rights reserved. Targetted drug delivery is currently an important topic in bio-nanotechnology research. However, at present an improved understanding of the underlying mechanisms is required to provide accurate and effective drug transportation in humans. In particular, to increase the blood-circulation time and to increase the interacting surface area between the drugs and the targeted cells. The study here focuses on determining the optimal location for a drug encapsulated in a nanocarrier in order to enhance the blood-circulation time. To illustrate the modelling, the anti-cancer drug Doxorubicin is adopted and liposome is assumed to be the nanocapsule. The Doxorubicin molecule is modelled as a sphere, which is assumed to be encapsulated in a spherical liposome of radius 50 nm, and the model consists of three systems, depending on the number of identical Doxorubicin molecules inside the liposome; one, two or three. In all cases, we determine the offset positions of the Doxorubicin from the centre of the liposomes, and also the angle between any two Doxorubicin molecules. Our findings predict the most stable configuration of a particular drug encapsulated in a capsule, and will prove useful as a guide in the design of other drug delivery systems involving small drug molecules inside a nanocapsule.